Identification of redundancy between human FcεRIβ and MS4A6A proteins points toward additional complex mechanisms for FcεRI trafficking and signaling. Issue 5 (7th December 2022) - Bitting, Katie; Hedgespeth, Barry; Ehrhardt‐Humbert, Lauren C.; Arthur, Greer K.; Schubert, Alicia G.; Bradding, Peter; Tilley, Stephen L.; Cruse, Glenn
Abstract: Background: Allergic diseases are triggered by signaling through the high‐affinity IgE receptor, FcεRI. In both mast cells (MCs) and basophils, FcεRI is a tetrameric receptor complex comprising a ligand‐binding α subunit (FcεRIα), a tetraspan β subunit (FcεRIβ, MS4A2) responsible for trafficking and signal amplification, and a signal transducing dimer of single transmembrane γ subunits (FcεRIγ). However, FcεRI also exists as presumed trimeric complexes that lack FcεRIβ and are expressed on several cell types outside the MC and basophil lineages. Despite known differences between humans and mice in the presence of the trimeric FcεRI complex, questions remain as to how it traffics and whether it signals in the absence of FcεRIβ. We have previously reported that targeting FcεRIβ with exon‐skipping oligonucleotides eliminates IgE‐mediated degranulation in mouse MCs, but equivalent targeting in human MCs was not effective at reducing degranulation. Results: Here, we report that the FcεRIβ‐like protein MS4A6A exists in human MCs and compensates for FcεRIβ in FcεRI trafficking and signaling. Human MS4A6A promotes surface expression of FcεRI complexes and facilitates degranulation. MS4A6A and FcεRIβ are encoded by highly related genes within the MS4A gene family that cluster within the human gene loci 11q12‐q13, a region linked to allergy and asthma susceptibility. Conclusions: Our data suggest the presence of either FcεRIβ or MS4A6A is sufficient for degranulation, indicating that MS4A6A could be an elusive FcεRIβ‐like protein in human MCs that performs compensatory functions in allergic disease. Abstract : We identify that MS4A6A is expressed in human mast cells and has high sequence homology to FcεRIβ. We show that MS4A6A contains a putative hemi‐ITAM that may function similarly to the FcεRIβ ITAM. We demonstrate that MS4A6A and FcεRIβ perform at least partially redundant roles in FcεRI complex trafficking and function.Abbreviations: Ag, antigen; Ca 2+, calcium ion; FcεRI, high‐affinity IgE receptor; ITAM, immunoreceptor tyrosine‐based activation motif; Lyn, Src family tyrosine kinase; MS4A6A, membrane‐spanning 4‐domains A6A; PLC, phospholipase C; Syk, spleen associated tyrosine kinase